2022
DOI: 10.1007/s10895-021-02884-0
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost Imaging of Fluorescent DNA in Agarose Gel Electrophoresis using Raspberry Pi cameras

Abstract: Low-cost analytical solutions built around microcomputers like the Raspberry Pi help to facilitate laboratory investigations in resource limited venues. Here, three camera modules (V1.3 with and without filter, as well as NoIR) that work with this microcomputer were assessed for their suitability in imaging fluorescent DNA following agarose gel electrophoresis. Evaluation of their utility was based on signal-to-noise (SNR) and noise variance metrics that were developed. Experiments conducted with samples were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…In order to achieve high-quality imaging, we selected low-cost but high-performance components. Previous publications have shown that single-board computers combined with matching cameras are a low-cost solution for biological microscopy [22], [36], [37]. For this reason, both versions, the standalone and the plug-in versions use Raspberry Pi 4k cameras.…”
Section: Concept and Methodsmentioning
confidence: 99%
“…In order to achieve high-quality imaging, we selected low-cost but high-performance components. Previous publications have shown that single-board computers combined with matching cameras are a low-cost solution for biological microscopy [22], [36], [37]. For this reason, both versions, the standalone and the plug-in versions use Raspberry Pi 4k cameras.…”
Section: Concept and Methodsmentioning
confidence: 99%
“…6X loading dye (Vivantis) was used to track deoxyribonucleic acid (DNA) migration and 0.005% RedSafe™ (iNtRON Biotechnology, Gyeonggi-do, Republic of Korea) was used to stained DNA during electrophoresis. Agarose gel electrophoresis was performed using PowerPac™ Basic Power Supply (BIO-RAD) according to Abid's protocol (25). PCR amplicons were visualized using ImageQuant™ LAS 500, GE Healthcare Bio-Sciences AB (Uppsala, Sweden).…”
Section: Effects Of Cordycepin On Messenger Ribonucleic Acid (Mrna) E...mentioning
confidence: 99%
“…Furthermore, the required instrumentation employed for fluorometric measurements has evolved in recent years from static designs mainly focused on laboratory assays towards more flexible, portable and handheld devices [10][11][12][13][14][15][16], which can be easily operated for in situ experiments. Thus, the increasing availability of the necessary components to build fluorometric detection devices, such as intense light sources with different excitation wavelengths (LEDs, fiber optic) [17,18] and compact micro-spectrometers for light analysis (C1280 MA) [19], and the existence of numerous computer-programmable microcontrollers (Raspberry Pi, Arduino) [20][21][22][23] allow the building of low-cost equipment [24][25][26] with unique features for in situ sample analysis with spectrofluorometric detection.…”
Section: Introductionmentioning
confidence: 99%